2006
DOI: 10.1016/j.rmed.2006.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral muscle composition and health status in patients with COPD

Abstract: These results indicate that impaired HS in COPD is related to the peripheral muscle changes characterized by less type I fibers proportion. The findings argue in favor of an important contribution of the systemic consequences on the HS in COPD independently from the airflow limitation severity, and help to explain the observation of the poor correlation between the degree of airflow limitation and SGRQ total score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 32 publications
4
19
0
4
Order By: Relevance
“…One additional publication, of which we were aware, incorrectly did not appear in the search results because fibre typing was not mentioned in the abstract 6. Of these 39 papers, 20 were excluded for the following reasons: 15 were false positive hits (eg, fibre type proportions were not studied or they were studied in skeletal muscles other than the quadriceps femoris), 2 had overlapping data (Montes de Oca et al 7 8 and Gosker et al 9 10) and 3 because of co-morbidity 6 11 12. The remaining 19 articles were included in the current study (table 1), all biopsies being obtained from the vastus lateralis.…”
Section: Resultsmentioning
confidence: 99%
“…One additional publication, of which we were aware, incorrectly did not appear in the search results because fibre typing was not mentioned in the abstract 6. Of these 39 papers, 20 were excluded for the following reasons: 15 were false positive hits (eg, fibre type proportions were not studied or they were studied in skeletal muscles other than the quadriceps femoris), 2 had overlapping data (Montes de Oca et al 7 8 and Gosker et al 9 10) and 3 because of co-morbidity 6 11 12. The remaining 19 articles were included in the current study (table 1), all biopsies being obtained from the vastus lateralis.…”
Section: Resultsmentioning
confidence: 99%
“…Data from human studies clearly indicate that atrophy of skeletal muscles is apparent in COPD and is specific to muscle fibre type IIA/IIx [72]. Furthermore, these abnormalities are related to respiratory function, exercise intolerance, health status, mortality and healthcare resource utilisation [73]. Muscle wasting is associated with loss of muscle strength, which in turn is a significant determinant of exercise capacity in patients with COPD independent of disease severity.…”
Section: Muscle Dysfunction and Malnutrition In Copdmentioning
confidence: 99%
“…Several studies have shown that the function and structure of skeletal muscle are altered in COPD patients and these abnormalities are related to respiratory function, exercise intolerance, health status, mortality and the utilization of healthcare resources [7,8,9]. Muscle wasting is associated with a loss of muscle strength and has therefore been identified as a significant determinant of mortality in COPD, independent of lung function, smoking and BMI [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Muscle wasting is associated with a loss of muscle strength and has therefore been identified as a significant determinant of mortality in COPD, independent of lung function, smoking and BMI [7,8,9]. …”
Section: Introductionmentioning
confidence: 99%